Managing Social Risks and Impacts from Hydropower Development : Sharing Experience from a Medium-Sized Dam Project in Vietnam - Nghi, Nguyen Quy; Lenihan, Martin H.; Saint-Pierre, Claude; Phuong, Nguyen Thi Minh; Dan, Phan Huyen (World Bank, Washington, DC, 2020)
The Trung Son dam is a medium-sized hydropower dam (260 megawatts) that was developed with the aim of achieving social and environmental sustainability. Experience gained from the Trung Son Hydropower Project can provide relevant information for dam projects of a similar size. This report is the result of a knowledge-sharing exercise conducted at the end of 2019 by the World Bank with Trung Son Hydropower Company Limited (TSHPCo) participation. The project benefitted from a decision-making process based on an adaptive management principle, defined by a framework of measures and implementation process. Detailed activities can evolve if they remained consistent with this framework. Experience gained from the Trung Son Hydropower Project demonstrates how relocation evolved, requiring continuous negotiations and engagement of all stakeholders to deal with unexpected problems. The critical management of downstream impacts during reservoir impoundment requires mitigation of specific risks. Assessed during the project preparation stage, downstream impacts associated with reservoir impoundment will be minimized through maintenance of a minimum environmental flow. The Trung Son reservoir area is rapidly evolving, with a newly created infrastructure network bringing both opportunities and challenges. To further provide support to local households and their communities, the scope of the corporate social responsibility of TSHPCo will need to be confirmed, and interaction with the local government is likely to continue over a long period of time.